Post-Stroke Depression and Estimated Glomerular Filtration Rate: A Prospective Stroke Cohort - Lin, Shasha (Neuropsychiatr Dis Treat, 2020)
PURPOSE: Post-stroke depression (PSD) is a frequent comorbidity in patients presenting with acute ischemic stroke. Impaired kidney function has been associated with depression in non-stroke subjects. We would like to evaluate whether the estimated glomerular filtration rate (eGFR) on admission is associated with the development of PSD. PATIENTS AND METHODS: Total of 268 patients with acute ischemic stroke were recruited and completed 1-month follow-up visit. eGFR was calculated from the serum creatinine value, race, age, and sex by using the chronic kidney disease epidemiology collaboration equation (CKD-EPI creatinine equation). The 17-item Hamilton Depression Scale was used to evaluate depression symptoms. Patients with a depression score of ≥7 were evaluated using the Structured Clinical Interview for Diagnostic and Statistical Manual of Mental Disorders, 4th edition, for diagnosing post-stroke depression at 1 month. Meanwhile, 114 normal control subjects were also recruited. RESULTS: Ninety-three (34.7%) patients were diagnosed as having PSD at 1 month. There was a significant intergroup difference in eGFR levels within 24 hrs after admission (F=13.608, p<0.001). The levels of eGFR within 24 hrs after admission were significantly lower in both non-PSD patients and PSD patients than in normal controls. In logistic regression, the level of eGFR (<82mL/min/1.73m(2)) was independently associated with increased risk of PSD even after adjusting for confounders (OR=2.328, 95% CI:1.092–4.965, p=0.029). CONCLUSION: Reduced eGFR was found to be correlated with the development of PSD and it suggests the need for greater attentions and potential interventions for depression in patients with stroke and with reduced eGFR.